Pore-scale, Computational Fluid Dynamics-based Simulation of Supercritical CO2-brine Flow through Porous Media - Jahan, Farjana (Curtin University, 2018)
Carbon Capture and Storage (CCS) is one of the effective methods to manage CO2 emissions to mitigate global warming and associated environmental changes. This thesis provide insight into this aspects emphasising on investigating the two-phase (brine and scCO2) flow behaviour, and advanced understanding on residual saturation, relative permeability, and capillary trapping capacity under various drainage and imbibition conditions using pore-scale numerical simulations based upon computational fluid dynamics (CFD).